Determinants of Tax Evasion with Religiosity as a Moderating Variable - Faridh Azhar Hakim; Sabaruddin Sabaruddin (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Tax evasion in Indonesia remains a serious problem, resulting in reduced state revenue. Various external factors, such as audit intensity, tax rates, and perceptions of fairness in the tax system, are believed to influence taxpayer behavior. On the other hand, internal factors, such as religiosity, also play a role in shaping individual attitudes and decisions regarding fulfilling tax obligations. This study uses a quantitative approach with an associative nature through a survey method. The research sample consisted of 97 individual taxpayers registered at the Pondok Aren Tax Office (KPP Pratama), selected using a nonprobability sampling technique with a purposive sampling approach. Data were analyzed using the Partial Least Squares (PLS) method with the assistance of SmartPLS software. The results of the study indicate that tax audits, tax rates, and tax fairness have a positive and significant influence on tax evasion. Furthermore, religiusity has been shown to moderate this relationship by strengthening the influence of each independent variable. These findings demonstrate that both external and internal factors play a significant role in shaping taxpayer behavior toward tax evasion.